FAKTOR-FAKTOR PENYEBAB KONFLIK PADA INTERNAL BROWNIES HACENDA - Ayyaash, Kharis Ibnu (PERFORMA, 2021)
The purpose of this research is to determine the factors that result in internal conflict in Hacenda Brownies. The two research variables are human factors and organizational factors, which include limited resources, task interdependence, and communication barriers. This research is a descriptive qualitative research with semi-structured interview as data collection method. The study informants include former Hacenda Brownies members, business facilitators, and human resources experts. Research results indicate that the main cause of internal conflict is human factor. This study discovers that the company members do not have good intentions in managing the company. Furthermore, the company’s limited financial power leads to lack of motivation. From communication perspective, the internal conflicts are mainly caused by poor work pattern and culture, as well as the interdependence between departments that comes as a result of the aforementioned human factors.